Contracting for health services: effects of utilization and quality on the costs of the Basic Package of Health Services in Afghanistan - Omid Ameli; William Newbrander (The World Health Organization, 2008)
OBJECTIVE: To research the effects of changes in health service utilization and quality on the costs of the Basic Package of Health Services (BPHS) in 13 provinces of Afghanistan. METHODS: The study grouped data from 355 health facilities and more than 4000 health posts into 21 data points that represented 21 different nongovernmental organization contracts for service delivery between April 2006 and March 2007. Data were pooled from five data sets on expenditure, service utilization, quality (i.e. client satisfaction and the availability of essential medicines and female health-care providers), pharmaceuticals, and security and remoteness scores. Pearson's partial correlation and multiple linear regression models were used to examine correlations between expenditure and other study variables. FINDINGS: Fixed costs were found to comprise most of the cost of BPHS contracts. There was no correlation between cost and utilization rate or security. The distance to the health facility was negatively correlated with costs (R² = 0.855, F-significance < 0.001). The presence of female health workers, indicative of good quality in this cultural context, was negatively correlated with security (r = -0.70; P < 0.001). There was a significant correlation between the use of curative services and client satisfaction but not between the use of preventive services and client satisfaction (R² = 0.389 and 0.272 for two types of health facilities studied). CONCLUSION: Access to health services can be extended through contracting mechanisms in a post-conflict state even in the presence of security problems. Service characteristics, geographical distance and the security situation failed to consistently explain, alone or in combination, the observed variations in per capita costs or visits. Therefore, using these parameters as the basis for planning does not necessarily lead to better resource allocation.